Further evidence on the stability of Islamic versus conventional banks in selected GCC countries from 1999 to 2015 - Abdul Karim, Norzitah; Syed Jaafar Alhabshi, Syed Musa; Kassim, Salina; Haron, Razali (IIUM Press, 2017)
Based on the theory of financial intermediation from both the perspective of original theory and the Islamic perspective, this paper aims to investigate the level of stability of the Islamic and the conventional banks. It also examines the different timing effects including the period of crisis on the stability of the Islamic and the conventional banks. The study evaluates 51 conventional banks and 50 Islamic banks in selected Gulf Cooperation Council (GCC) using data from the Bankscope database over the period of 1999 to 2015. The study employs two-sample t-test with unequal variance t-test and the non-parametric Wilcoxon test and Mann-Whitney test to compare i) mean of Islamic versus conventional banks over different timing period ii) mean of tested period versus other periods for each of the Islamic and conventional banks. The study suggests that the GCC Islamic banks are more stable compared to their conventional counterparts. However, in testing different timing period, only GCC conventional banks seem to be affected by the crisis period while Islamic banks are less prone to the crisis.. Findings of this study contribute to the literature and fill the gap towards extending the theory of financial intermediation through empirical works of investigating the stability of the Islamic and the conventional banks.